1973
DOI: 10.1111/j.1471-0528.1973.tb02976.x
|View full text |Cite
|
Sign up to set email alerts
|

A Serial Study of Changes Occurring in the Oral Glucose Tolerance Test During Pregnancy

Abstract: Summary Nineteen healthy pregnant women with no family history of diabetes took part in a serial study in which they had a standard 50 g. oral glucose tolerance test (OGTT) at 10, 20, 30 and 38 weeks gestation and again 10 to 12 weeks after delivery. While every test result remained within “normal” limits as defined by any of the standard criteria, subtle and progressive changes in the shape of the glucose response curve were shown to occur throughout pregnancy. These changes in shape were evaluated by means o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
38
3
2

Year Published

1979
1979
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(54 citation statements)
references
References 10 publications
11
38
3
2
Order By: Relevance
“…Similarly, in lowlanders acclimatised to high altitude, glucose utilisation is increased 18 . The ®nding that at sea level fasting glucose decreased by about 10% during the ®rst trimester of pregnancy and did not change thereafter is compatible with the results of previous studies in England 4 and the United States 5 . The suggested causes of this decrease in fasting plasma glucose include haemodilution in early pregnancy 19 and increased insulin secretion in the third trimester 20 .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similarly, in lowlanders acclimatised to high altitude, glucose utilisation is increased 18 . The ®nding that at sea level fasting glucose decreased by about 10% during the ®rst trimester of pregnancy and did not change thereafter is compatible with the results of previous studies in England 4 and the United States 5 . The suggested causes of this decrease in fasting plasma glucose include haemodilution in early pregnancy 19 and increased insulin secretion in the third trimester 20 .…”
Section: Discussionsupporting
confidence: 80%
“…Maternal hyperglycaemia is associated with fetal macrosomia 2 , whereas in fetal growth restriction maternal plasma glucose is decreased 3 . Studies at sea level have demonstrated that maternal fasting plasma glucose concentration drops during the ®rst trimester by 10%-15%, compared with non-pregnant controls, and remains low throughout pregnancy 4,5 . Studies at high altitude in non-pregnant women have reported that, compared with those at sea level, fasting plasma glucose in natives is decreased 6 and in acclimatised subjects is decreased 7,8 , unchanged 9 , or even increased 10 .…”
Section: Introductionmentioning
confidence: 99%
“…They also reported an inverse relationship between serum human placental lactogen level and glucose disposal rate, but they found no relationship with serum estradiol, progesterone, or cortisol levels. Similarly, in a series of glucose tolerance tests in pregnancy, Lind et al (23) found a lower rise in plasma glucose in the first trimester compared with observations in the nonpregnant state or later in gestation.…”
Section: Falling Insulin Requirement In Pregnancymentioning
confidence: 99%
“…The parameter that best reflected the decrease in glucose tolerance was the level 60 minutes after glucose injection, which at 33 gestational Next, the changes in plasma IRI after 75 g GTT were observed. As previously mentioned, the fasting plasma IRI level during pregnancy tends to increase (Spellacy and Goetz, 1963) and the post-glucose loading response is augmented (Daniel et al 1974;Kalkhoff et al1970;Lind et al 1973;Spellacy and Goetz, 1963;Spellacy et al1965;. During pregnancy, the anabolic phases in the mother and the fetus are gradually potentiated, while the accelerated secretion of corticosteroids and hPL by the mother after the 20th gestational week brings about a relative potentiation of maternal catabolism (Freinkel et al1979).…”
Section: Discussionmentioning
confidence: 68%